How do size distributions relate to concurrently measured demographic rates? Evidence from over 150 tree species in Panama. (11th April 2016) - Lima, Renato A.F.; Muller-Landau, Helene C.; Prado, Paulo I.; Condit, Richard
Abstract: In stable populations with constant demographic rates, size distributions reflect size-dependent patterns of growth and mortality. However, population growth can also affect size distributions, which may not be aligned with current growth and mortality. Using 25 y of demographic data from the 50-ha Barro Colorado Island plot, we examined how interspecific variation in diameter distributions of over 150 tropical trees relates to growth–diameter and mortality–diameter curves and to population growth rates. Diameter distributions were more skewed in species with faster increases/slower decreases in absolute growth and mortality with diameter and higher population growth rates. The strongest predictor of the diameter distribution shape was the exponent governing the scaling of growth with diameter (partial R 2 = 0.20–0.34), which differed among growth forms, indicating a role of life history variation. However, interspecific variation in diameter distributions was also significantly related to population growth rates (partial R 2 = 0.03–0.23), reinforcing that many populations are not at equilibrium. Consequently, although fitted size distribution parameters were positively related to theoretical predictions based on current size-dependent growth and mortality, there was considerable deviation. These analyses show that temporally variable demographic rates, probably related to cyclic climate variation, are important influences on forest structure.